Potency assays for novel T-cell-inducing vaccines against malaria. - Reyes-Sandoval, A; Pearson, F; Todryk, S; Ewer, K (2009)
The complex life cycle of the malaria parasite involves several developmental stages in the mammalian host that provide opportunities for vaccine intervention. The effector arm of the immune response that protects against malaria is specific for each stage of the parasite life cycle. While CD4+ and CD8+ T-cells are required to mediate protection during the liver stage, antibodies play a major role before parasite entry into the liver and during the blood stage. Induction of cytotoxic T-cells or those producing IFNgamma has become a major goal for T-cell-inducing vaccines, and the liver stage is currently one of the preferred targets for malaria vaccine development. T-cells can effectively be primed by several vaccine strategies, including recombinant vectors. A wide range of such vectors is currently available and their use alone or in combination induces high frequencies of antigen-specific T-cells in animal models and humans. Therefore, traditional potency assays, such as the highly sensitive ex vivo and cultured ELISPOT, are being complemented by less sensitive, but more flexible techniques, such as flow cytometry, which allows characterization of multifunctional antigen-specific T-cells following vaccination.